Development of tax procedural law and sectoral case law in selected countries - Vozel, Tjaša (Central European Public Administration Review, 2018)
The purpose of this paper is to examine the development of the Slovenian Tax Procedure Act and amendments thereto until 2017, in order to broaden the field knowledge on tax procedures within the administrative system as a whole. The Tax Procedure Act provides the general framework of the procedural tax system in Slovenia. The first version of the Tax Procedure Act (ZDavP) was adopted in 1996 and followed by five amending acts until the adoption of the second version (ZDavP-1) in 2004. The third and currently applicable version of the Tax Procedure Act (ZDavP-2) has been subject to over ten amendments so far. Furthermore, the study aims to compare the development of tax procedure in Slovenia and Sweden. Based on the normative and comparative analyses, review of domestic and foreign literature, and case law analysis, the advantages and disadvantages of the development of tax procedure in Slovenia were identified. The amendments analysed contributed mainly to simplifying the tax procedure, reducing red tape, decreasing costs, improving the efficiency of the tax authorities, and providing greater legal certainty for the taxpayers. Most changes to the Tax Procedure Act involved the personal income tax. An empirical study of the case law of the Administrative, Supreme and Constitutional Courts in selected period further showed that errors were mainly detected in relation to substantial violation of procedural requirements rather than incorrect application of substantive law. The study contributes to administrative and legal science and the tax profession as such. The results can be useful when drafting new tax procedural legislation to improve its effectiveness.
Keywords: davčni postopek; davčno pravo; davki; Slovenija